Chloroplast DNA markers for Echinochloa taxa. (23rd October 2017) - Zhang, J‐P; Fu, F; Liu, C; Lin, Z‐X; Wang, Y‐Y; Ye, C‐Y; Lu, Y‐L
Summary: The genus Echinochloa (Poaceae) includes numerous problematic weeds over a wide range of ecoregions in the world. To date, molecular markers for species identification and assessing phylogenetic relationship are still limited in the genus Echinochloa . In this study, we developed seven chloroplast molecular markers based on divergent chloroplast regions of E. crus‐galli and E. oryzicola . Furthermore, Marker #1 ( psbA ) was examined in more than 200 Echinochloa accessions and a phylogenetic tree grouped these Echinochloa accessions into four clades. Additionally, two different E. crus‐galli varieties ( E. crus‐galli var. crus‐galli, E. crus‐galli var. praticola ) and E. colona were successfully distinguished by this marker. The developed molecular markers contribute to better identification of Echinochloa taxa.